2020
DOI: 10.1186/s13756-020-00742-5
|View full text |Cite
|
Sign up to set email alerts
|

Poor infection prevention and control standards are associated with environmental contamination with carbapenemase-producing Enterobacterales and other multidrug-resistant bacteria in Swiss companion animal clinics

Abstract: Background: Intensive medical care in companion animal clinics could pose a risk for the selection and dissemination of multidrug-resistant organisms (MDROs). Infection prevention and control (IPC) concepts are key measures to reduce the spread of MDROs, but data on IPC standards in companion animal clinics is sparse. The study assessed IPC standards in seven companion animal clinics and practices in Switzerland by structured IPC audits and combined results with environmental MDRO contamination and MDRO carria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 56 publications
4
43
0
1
Order By: Relevance
“…An extrapolation of our results to ICU settings of other veterinary clinics is thus not possible. Of note, the companion animal clinic included in this study showed the lowest environmental ARM contamination and the highest IPC standards among three large referral clinics in Switzerland in a recent study, suggesting that the frequency of ESBL-E transmission chains observed in this study might not be overestimated [40]. However, the present study also showed considerable variations in the ESBL-E detection between sampling days.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…An extrapolation of our results to ICU settings of other veterinary clinics is thus not possible. Of note, the companion animal clinic included in this study showed the lowest environmental ARM contamination and the highest IPC standards among three large referral clinics in Switzerland in a recent study, suggesting that the frequency of ESBL-E transmission chains observed in this study might not be overestimated [40]. However, the present study also showed considerable variations in the ESBL-E detection between sampling days.…”
Section: Discussionsupporting
confidence: 43%
“…Such long carriage periods could additionally contribute to the risk of spreading of ESBL-E in the household environment [28]. Of note, environmental contamination in household 1 for ESBL-E was much higher than at most of the sampling days in the ICU in the investigated clinic (3%, range: 0-24%), and higher than recently reported for environmental samples collected in seven companion animal clinics and practices in Switzerland (0-2% of the environmental specimens were ESBL-E positive) [40]. Although only two households were investigated in this study, our results are alarming and highlight the need to develop evidence-based recommendations for the handling of ESBL-E colonized animals in the household environment.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…It is not fully understood how nosocomial infections are caused by K. pneumoniae. The possible reasons for the spread of nosocomial infections in general and those caused by K. pneumoniae, in particular, is related to the health setting and its hygienic measures [21] and secondly due to the ability of K. pneumoniae to acquire resistant genes via horizontal gene transfer facilitated by plasmids and mobile genetic elements [22].…”
Section: Discussionmentioning
confidence: 99%
“…Enterobacteriaceae producing carbapenemase ( bla NDM-1 and bla OXA-48 ) have been isolated from companion animals like dogs, cats, and horses in the USA, Germany, Greece and UK [ 66 , 72 , 73 , 74 , 75 ]. Another recent study in Switzerland reported the isolation of various carbapenemase-producing Enterobacteriales in companion animal clinics mainly associated with poor clinical practices [ 76 ]. The isolation of CRE in companion animals brings the attention to reconsider the use of any off-label use of carbapenems in the veterinary medicines.…”
Section: Companion Animalsmentioning
confidence: 99%